Tool temperature prediction in end milling using voxel model-based simulation - Rei MATSUMURA; Isamu NISHIDA; Keiichi SHIRASE (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
In end milling operations, the tools are exposed to high temperatures and high pressures, which inevitably causes the tool wear progress. It is well known that the tool wear progress strongly depends on the temperature of cutting edge. In this study, the thermal analysis to predict cutting temperature is performed by modeling heat transfer, heat input and heat dissipation between the tool and the workpiece based on the voxel model in which the workpiece and the tool are modeled in Cartesian and cylindrical coordinate systems, respectively. The heat input is estimated by the cutting energy predicted by machining simulation with the instantaneous cutting force model. To verify the validity of the proposed cutting temperature simulation method, the predicted cutting temperature was compared with the experimental results in which tool temperatures in end-milling operation measured by a thermocouple thermometer embedded inside the end mill. The predicted maximum temperature and temperature transient responses were in qualitative agreement with the measured results.